Development of teaching materials for evaluating history learning to improve students' critical thinking skills - Fahruddin, Fahruddin; Kurniawanti, Merci Robbi; Nurgiansah, T Heru; Gularso, Dhiniaty (Intelektual Pustaka Media Utama, 2025)
This study aims to find out: firstly, the qualifications for developing teaching materials to evaluate observation-based history learning and secondly the level of students' critical thinking skills. The results of this research contribute to improving students' critical thinking skills through the development of teaching materials. This research method is development (RD). The sample used was History Education students at PGRI Yogyakarta University. The instruments used were questionnaires and interview guidelines. The data analysis technique used is descriptive qualitative to explain observational and interview data, and quantitative descriptive statistical analysis techniques to measure the validity of experts and the effectiveness of teaching materials. This study resulted in firstly, expert tests showed content standards showed a score of 90%, language standards showed a score of 91.67%, and display standards showed a score of 81.67%; all three scores showed excellent and valid meaning, secondly, the average percentage of critical thinking indicators was 80.77% for the experimental class and 70.30% for the control class. The numbers in the experimental class show high effectiveness, so the results of this study conclude that the teaching materials for historical learning evaluation developed are very effective in improving students' critical thinking skills.